Design and simulation of four-stroke engines - Blair, Gordon P. (Society of Automotive Engineers Warrendale, 1999)
Provides design assistance with the actual mechanical design of an engine in which the gas dynamics, fluid mechanics, thermodynamics, and combustion have been optimized so as to provide the required performance characteristics such as power, torque, fuel consumption, or noise emission.
Keywords: Four-stroke cycle engines -- Design and construction